MODEL SUPERVISI AKADEMIK BERBASIS COACHING: STRATEGI TRANSFORMATIF MENINGKATKAN PROFESIONALISME GURU DALAM PEMBELAJARAN DIFERENSIASI - Pattinasarany, Theophanie (STKIP Subang, 2026)
The transition to the Education 5.0 paradigm requires teachers to be able to accommodate student heterogeneity through differentiated instruction. However, field practice shows that teachers often face challenges in assessing students’ learning readiness, interests, and learning profiles. Conventional academic supervision, which tends to be administrative and instructive in nature, is considered ineffective in fostering teachers’ transformative awareness. Therefore, a shift in the supervision model toward a coaching approach that prioritizes partnership, creative processes, and the maximization of professional potential is necessary. This study aims to analyze the effectiveness of a coaching-based academic supervision model (using the TIRTA framework or the GROW model) in enhancing teachers’ professional competencies, particularly regarding the design, implementation, and evaluation of differentiated instruction encompassing content, process, and product differentiation. This study employs a qualitative approach using the case study method. Data were collected through classroom observations, in-depth interviews with supervisors and teachers, and documentation of differentiated lesson plans (RPP). Data analysis techniques were conducted through data reduction, data presentation, and drawing conclusions to examine changes in teachers’ mindsets and instructional behaviors before and after the coaching intervention. The study results indicate that coaching-based academic supervision is capable of creating a safe space for dialogue where teachers can reflect on technical challenges in the classroom. Through reflective probing questions from the supervisor, teachers were able to identify differentiation strategies most relevant to their students’ characteristics. Significantly, this model enhanced teachers’ self-efficacy, flexible classroom management skills, and willingness to innovate in delivering inclusive instructional content.